Design and stress analysis of bevel line gears with vertical flank suitable for micro machining - Shao, Yanjie (Strojniški vestnik, 2024)
The line gear (LG) exhibits promising applications in micromachinery owing to its simple structure and minimal teeth count. This paper aims to advance the meshing theory of LG and introduce a conical LG tooth configuration specifically tailored for micro-machining that is capable of driving with high performance. Based on the meshing principle of LG, a conical line gear pair with vertical flank (VFLG) of the driving gear was designed. Subsequently, adhering to the curvature non-interference principle that no local interference occurs in the meshing process and the specified range of fitting error in one direction, the design parameters for LG were determined. A comparison of the contact stress between two sets of different contact line types revealed the distinct advantage of VFLG with parameters identical to those of traditional LG. The experimental results conclusively demonstrate a transmission ratio error of 0.004, affirming the feasibility of the design. The curvature non-interference design formula proposed in this paper refines the LG design theory, and the novel LG design method presented holds significant implications for subsequent micromachining.
Keywords: analiza napetosti; bevel gears; line gears; linijski zobniki; meshing theory; micro machining; mikroobdelava; stožčasti zobniki; stress analysis; teorija odsotnosti interferenc; teorija ubiranja